2015
DOI: 10.1371/journal.pone.0145036
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Prototyping of a High Sensitivity Graphene Based Glucose Sensor Strip

Abstract: A rapid prototyping of an inexpensive, disposable graphene and copper nanocomposite sensor strip using polymeric flexible substrate for highly sensitive and selective nonenzymatic glucose detection has been developed and tested for direct oxidization of glucose. The CuNPs were electrochemically deposited on to the graphene sheets to improve electron transfer rates and to enhance electrocatalytic activity toward glucose. The graphene based electrode with CuNPs demonstrated a high degree of sensitivity (1101.3±5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Therefore, the size, population density, and morphology of the CuNCs can be controlled by the variables mentioned above. For our research, in order to simplify the deposition process while achieving the optimal size and population density of the CuNCs, the electrodeposition solution concentration, pH, temperature, and deposition time were held constant at the optimal values established in our previous study52. The pulse current intensity, the only variable introduced in the newly employed pulse electroplating technique, was manipulated in favor of electroplating optimal CuNCs.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the size, population density, and morphology of the CuNCs can be controlled by the variables mentioned above. For our research, in order to simplify the deposition process while achieving the optimal size and population density of the CuNCs, the electrodeposition solution concentration, pH, temperature, and deposition time were held constant at the optimal values established in our previous study52. The pulse current intensity, the only variable introduced in the newly employed pulse electroplating technique, was manipulated in favor of electroplating optimal CuNCs.…”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical properties of the modified graphene electrodes were inspected by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and amperometry with a LOD of 0.025-0.9 mM. 135 An electrochemical immunosensor for cancer biomarker a-fetoprotein by using graphene and chitosan to modify screen printed carbon electrode where graphene acted like an electron transfer nanomaterials which can respond to 0.02 ng/mL of a-fetoprotein. 129 Using an electrochemical impedance spectroscopy, Kailasiya et al have demonstrated a sensitive biosensor based on antibody and GO on glassy carbon (GC) electrode for the detection of platelet-derived microparticles (the blood samples obtained from patients diagnosed with acute infarction).…”
Section: Electrochemical Based Biosensing Systemmentioning
confidence: 99%
“…Electrical sensors are electronic devices capable of detecting physical quantities in their environment and convert them into measurable electrical signals that can be displayed by the monitor [1][2][3]. Sensors can be designed, fabricated, and employed for various applications subject to the physical quantity to be measured [4][5][6][7][8]. Depending on the type, sensors can measure specific changes in the properties of different materials such as liquids and gases.…”
Section: Introductionmentioning
confidence: 99%